Circulating tumor cells and microemboli can differentiate malignant and benign pulmonary lesions - Mascalchi, Mario (J Cancer, 2017)
The presence of circulating tumor cells (CTC) or microemboli (CTM) in the peripheral blood can theoretically anticipate malignancy of solid lesions in a variety of organs. We aimed to preliminarily assess this capability in patients with pulmonary lesions of suspected malignant nature. We used a cell-size filtration method (ScreenCell) and cytomorphometric criteria to detect CTC/CTM in a 3 mL sample of peripheral blood that was taken just before diagnostic percutaneous CT-guided fine needle aspiration (FNA) or core biopsy of the suspicious lung lesion. At least one CTC/CTM was found in 47 of 67 (70%) patients with final diagnoses of lung malignancy and in none of 8 patients with benign pulmonary nodules. In particular they were detected in 38 (69%) of 55 primary lung cancers and in 9 (75%) of 12 lung metastases from extra-pulmonary cancers. Sensitivity of CTC/CTM presence for malignancy was 70.1% (95%CI: 56.9-83.1%), specificity 100%, positive predictive value 100% and negative predictive value 28.6% (95%CI: 11.9-45.3%). Remarkably, the presence of CTC/CTM anticipated the diagnosis of primary lung cancer in 3 of 5 patients with non-diagnostic or inconclusive results of FNA or core biopsy, whereas CTC/CTM were not observed in 1 patient with sarcoidosis and 1 with amarthocondroma. These results suggest that presently, due to the low sensitivity, the search of CTC/CTM cannot replace CT guided percutaneous FNA or core biopsy in the diagnostic work-up of patients with suspicious malignant lung lesions. However, the high specificity may as yet indicate a role in cases with non-diagnostic or inconclusive FNA or core biopsy results that warrants to be further investigated.